Trust evaluation model for distributed home photovoltaic collection scenarios in new power system - Li LI; Xiaolong WANG; Zhixin ZHANG; Rongliang SHI; Xu GUO (Tongxin xuebao)
Aiming at the problem that the existing sensor network trust evaluation model could not be directly applied to the new power system distributed home photovoltaic collection scenario, which was difficult to meet the require-ments of strong computing power and high defense power of the new power system, a distributed dynamic trust evaluation model based on multi-index detection was proposed.Firstly, the communication trust evaluation based on Bayes was carried out according to the historical interaction of terminal acquisition nodes.Then, the currently col-lected data was evaluated by perceptual trust based on its historical data support degree and regional trust based on probability density.Finally, the entropy weight method was used to decentralize each trust module’s values dynamically.The node activeness and double reward and punishment mechanism were introduced to calculate the comprehensive trust value and realize the dynamic update.The experimental results show that the four levels of the trust evaluation model are suitable for the new power system environment and can be used to detect the distributed in 20 round period of household photovoltaic power generation collection given the signal in the scene, achieve dynamic and accurate trust evaluation of abnormal nodes in the case of physical environment factors, equipment quality factors, human misoperation and malicious intrusion.